Abandoned children in China: the son-preference culture and the gendered-differentiated impacts of the one-child policy - Mei Yang; Xinming Xia; Yi Zhou (Humanities & Social Sciences Communications, 2023)
China has experienced an upsurge in child abandonment since the late 1970s in parallel with its one-child policy (OCP) and market reforms. Due to the scarcity of individual-level data, the literature focuses on informal adoption and child trafficking. This study first demonstrates the spatial-temporal trends of child abandonment across over 100,000 self-reported cases spanning 40 years in China collected from an internet platform. We then examine how the OCP and the long-established clan culture influence the incidence of child abandonment at the provincial level. We further compare whether the influences vary across genders. The results indicate that a tougher OCP penalty increases child abandonment, particularly the abandonment of girls. The influence of the OCP on girl abandonment is weaker in provinces with a strong clan culture, where sex ratios at birth are more unbalanced due to an increased incidence of gender-selective abortions.